UNILATERAL CONTRACT IN THE COOPERATION BETWEEN BPJS HEALTH AND HOSPITALS: AN ANALYSIS OF PARTY IMBALANCE - Rahmad Hidayat Harahap, (Proceeding International Conference on Social Sciences, 2026)
The cooperation between BPJS Kesehatan (Indonesia’s National Health Insurance Agency) and hospitals represents a form of public–private partnership (PPP) with distinctive characteristics within the national health system. In practice, the contractual relationship between these two entities is often perceived as placing BPJS Kesehatan in a more dominant position. This occurs because BPJS simultaneously functions as regulator, purchaser of health services, and supervisor of contract implementation. This study aims to examine the legal characteristics of the cooperation contract, assess the extent to which unilateral elements emerge within its regulatory framework, and analyze the implications of such imbalance for hospital autonomy, legal certainty, and the economic sustainability of healthcare institutions. Using a normative juridical method, this research reviews primary legal sources such as Law No. 24 of 2011 on BPJS, BPJS Regulation No. 1 of 2014 concerning Cooperation with Healthcare Facilities, and Article 1338 of the Indonesian Civil Code. These sources are supported by secondary literature on administrative law theory and public contract concepts. The analysis shows that the cooperation contract between BPJS Kesehatan and hospitals tends to be substantively unbalanced, mainly due to the discretionary authority of BPJS to interpret, modify, and even terminate the contract unilaterally. This condition weakens the bargaining position of hospitals and may create structural inequality in the implementation of the national health insurance system. These findings pose challenges to the principles of contractual justice and good governance, particularly with regard to fairness, transparency, and accountability. This research recommends restructuring the cooperation into a more equitable bilateral administrative contract and offers conceptual contributions to the development of public contract law and reform of the BPJS system in Indonesia.